Blended Learning Based Inquiry Collaborative Tutorial Model for Physics Students - Lovy Herayanti; Wahono Widodo; Endang Susantini; Gunawan Gunawan (JPPS (Jurnal Penelitian Pendidikan Sains), 2019)
Blended learning is basically a combination or mixture found in learning practice. Blended learning is a further development of the e-learning method, namely learning methods that combine e-learning systems with conventional or face-to-face methods. The purpose of this study was to determine the validity of the models and learning devices both in terms of content and model constructs, as well as to find out student responses to the model developed. The model developed was validated through a forum mechanism, namely, focus group discussion (FGD) which was followed by researchers and experts. The suggestions and improvements generated from the validation activities were then followed up to revise the Inquiry Collaborative Tutorial-based blended learning model. Inquiry Collaborative Tutorial-based blended learning model and learning devices developed in this study have met valid criteria in content and construct. Valid content because there are elements of need and novelty, as well as valid constructs because there is consistency between parts of the model and there is relevance between the models developed with learning theories that underlie it. In general, the average student responds positively to the blended learning model based on the Inquiry Collaborative Tutorial. The model applied is considered to provide opportunities for students to actively participate.